Avaliação do zooplâncton em poças temporárias na região semiárida da Caatinga – a importância do banco de ovos - Morais-Júnior, Cláudio Simões (Universidade Federal de São Carlos, 2023)
The construction of small reservoirs for storing rainwater is a very common action in the semi-arid region of the “Caatinga” biome. Due to the low rainfall characteristic in this climate region, these reservoirs become temporary. Likewise, due to their intermittence plus reduced size and depth, these water bodies are classified as temporary ponds among the scientific community. Faunistic diversity in these environments includes zooplankton, which has functional characteristics for survival and dispersion among such aquatic environments. The present study aims to evaluate the patterns of survival and dispersal of zooplankton with a focus on their dormant structures. For this, four temporary ponds were chosen in the semi-arid region of Pernambuco, in the Municipality of Custódia. In them, the egg bank was mapped in all its extension, looking for patterns of alpha and beta diversity, as well as evaluating the influence of the water column extension on the eggs produced by the different species and on the hatching process from the resistance structures. Subsequently, the ecological succession of the zooplankton community was evaluated in situ throughout the entire hydroperiod, evaluating patterns of alpha and beta diversity, as well as variations in species abundance. Finally, sediment samples were collected to be used as dispersal propagules in a colonization experiment of water bodies, simulated in mesocosms. The egg bank portion with the highest zooplankton species diversity and abundance in the temporary pond’s central region, although cladocerans had similar egg abundances in the whole pond basins. Once resting eggs are stimulated to hatch during rainy season originating a zooplankton community initially formed by copepods and rotifers. Along the time the community become richer reaching a peak around middle rainy season in June. Soon after, ponds gradually loose water tending to the eminent collapse. This leads to significant changes in species composition. Resistance eggs produced by these communities are capable to colonize other water bodies with high efficiency, thus increasing species richness in communities already formed, as well as in sterile environment. Egg banks are structurally distinct with variable richness and density spatial patterns, what can directly influence species dispersion patterns among the environments, as well as on their recruitment to the water column.
Assessment of zooplankton in temporary pools in the semi-arid region of the Caatinga – importance of the egg bank
Keywords: Sucessão ecológica; Comunidades zooplanctônicas; Estágios dormentes; Eclosão de ovos; Ecological succession; Zooplankton assemblages; Dormant stages; Eggs hatching; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES